Iron in the biology and treatment of gastrointestinal cancer - Ng, Oliver C.T. (2019)
Background Iron is intimately related to the biology and pathology of gastrointestinal cancer with both iron excess and iron deficiency influencing disease. This thesis examines the biological and clinical effects of iron replacement in gastrointestinal cancer.